2008
DOI: 10.1002/ajmg.b.30592
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 1 gene (CNR1) and susceptibility to a quantitative phenotype for hebephrenic schizophrenia

Abstract: Functional alterations of components of the endogenous cannabinoid system, in particular of the cannabinoid receptor 1 protein (CB1), are hypothetical contributors to many of the symptoms seen in schizophrenia. Variants within the cannabinoid receptor 1 gene (CNR1) have been shown to be directly associated with the hebephrenic form of schizophrenia in a Japanese population. This finding, however, has yet to be replicated. In the present study we sought to study the same (AAT)n-repeat microsatellite of the CNR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 24 publications
(29 reference statements)
0
56
1
3
Order By: Relevance
“…These findings support the hypothesis that variation in the CNR1 gene confers risk for a hebephrenic type of schizophrenia. 29 However, this study did not confirm the association between (AAT)n polymorphism and schizophrenia as a broad phenotype.…”
Section: Cnr1 Gene Polymorphisms and Occurrence Of Schizophrenia And contrasting
confidence: 62%
See 1 more Smart Citation
“…These findings support the hypothesis that variation in the CNR1 gene confers risk for a hebephrenic type of schizophrenia. 29 However, this study did not confirm the association between (AAT)n polymorphism and schizophrenia as a broad phenotype.…”
Section: Cnr1 Gene Polymorphisms and Occurrence Of Schizophrenia And contrasting
confidence: 62%
“…Chavarria-Siles et al 29 replicated the findings of Ujike et al 16 in a population of 244 subjects with a DSM-IV diagnosis of schizophrenia and 481 family members recruited from psychiatric hospitals and clinics in the Central Valley of Costa Rica. The study found a positive correlation of prominent lifetime scores for disorganization and negative symptoms (hebephrenia dimension) with the (AAT)n polymorphism (multiallelic p = 0.0368).…”
Section: Cnr1 Gene Polymorphisms and Occurrence Of Schizophrenia And mentioning
confidence: 60%
“…We found a significant interaction to exist between the two haploblocks of this gene (epistasis), and this may have an impact on the expression of CB1 receptor (Zhang et al, 2004). Schizophrenia has also been associated with the CNR1 gene, although with conflicting results (Levinson et al, 2000;Leroy et al, 2001;Zhang et al, 2004;Chavarria-Siles et al, 2008;Hamdani et al, 2008). It is important to note that schizophrenic patients compared with depressed subjects, score just as high for neuroticism but even lower for agreeableness (Bagby et al, 1997), particularly if they have co-morbid substance abuse disorder (Reno, 2004).…”
Section: Discussionmentioning
confidence: 83%
“…This genetic region has been linked to schizophrenia (Levinson et al, 2000;Leroy et al, 2001), but this has not been replicated, although recently the CNR1 gene has been associated with specific symptoms or with non-responder status for antipsychotic drugs rather than with schizophrenia as a disorder (Chavarria-Siles et al, 2008;Hamdani et al, 2008). There are more convincing results on the association of the CNR1 gene and substance abuse disorders (Zhang et al, 2004;Zuo et al, 2007;Chen et al, 2008), although there is a negative replication study (Herman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, convergent findings suggest that CNR1 signaling may be abnormal in patients with this brain disorder, even if the functional specificity of these anomalies is unclear (Dalton et al, 2011). Moreover, CNR1 has been inconsistently associated with diagnoses of schizophrenia (Chavarría-Siles et al, 2008;Seifert et al, 2007), and genetic variability and cannabis use appear to interact in conferring risk for psychosis (Caspi et al, 2005;van Winkel et al, 2011b, Di Forti et al, 2012. Interestingly, CNR1 signaling has been implicated in dopamine signaling (Bloomfield et al, 2014), which is centrally linked with schizophrenia (Weinberger et al, 2001).…”
Section: Discussionmentioning
confidence: 99%